Alat Pengontrol Kekeruhan Air Kolam Dan Pemberi Makan Lele - Efrizon efrizon; Yulastri yulastri; Ifandi ifandi (Teknik Elektro Politeknik Negeri Padang, 2018)
Many innovations that have been implemented by catfish breeders, where catfish are of a distinctive taste and make it a very popular thing in catfish lovers. Many farmers compete to get great seeds and are capable of producing good development and fast. This tool designer creates a tool that can be used by catfish farmer through a prototype in order to read and control the level of turbidity and automatic feeder. The level of turbidity is very important for catfish growth, where the level turbidity can band catfish growth. This tool is supported by supporting devices such as turbine sensors, ultrasonic sensors, RTC DS1307, servo motors and Atmega328 microcontrollers. The Turbinity sensor is used to measure the level of water that is going to go out from the fishpond. Furthermore, this research is also facilitated by an automatic feeder that will run according to the time that has been set by a farmer. When the feeding time is comming the servo motor will open the feed valve for a while based on food requirements time. Beside that the automatic feeder is also facilited by ultrasonic sensors that can be used for monitoring the availability of feeds when the feed in minimum the level will be active the buzzer or beeb.